Use of University Library Web as a Marketing Tool in Sri Lanka - Ranasinghe, S.; Konpola, K.W.A.M. (Proceedings of 1st International Conference on Library and Information Management, 2016)
Attached

Marketing is not a new concept for libraries. The concept o f marketing has been transferred from business world to service or to non for profit organizations since 1970s. Presently almost all libraries apply the concept o f marketing for number o f reasons. Common strategies in practice are advertising through various media and public relations. With the development and adoption of technologies, most libraries all over the world are exploiting the web as a tool for marketing. The stpdy aimed at finding out whether the university libraries in Sri Lanka embraced with ICT in implementing marketing strategies through intemet/web and present state o f use o f web sites as a marketing tool. Present study involved a survey based on evaluation o f web sites o f university libraries in Sri Lanka. Web sites o f Universities under University Grants Commission were the population (15) and the whole population was selected as the sample. The researchers used four major criteria with sub categories adopted from Kaur, Kiran in 2 0 0 9 . University home pages and library home pages were assessed. Each and every website was evaluated for visibility, Networking, information and consultations and comments. Only a half (53% ) o f the universitylibrary web sites possess the direct links to university home page. 47% are hidden and are under Academic or some other heading and have to use several steps to reach the web page. 53% o f library web sites have provided links to other external networks such as to universities, Library associations. Almost all the libraries have provided information regarding their collection, services and facilities. In all the library web sites e mail o f the library and staff were indicated but only 40% have gone beyond that service such as “Ask - A service” or message service. It seems that marketing process is not carried out through the web in an effective manner though there are some adoptions and initiatives to use the websites as a tool for marketing. It was strongly felt that library professionals in Sri Lanka should pay more attention to market their libraries through web. They should reap maximum benefit from the ICT and, marketing concepts should be warmly accepted and introduced by the librarians
Keywords: Marketing; library marketing; University libraries; Web applications; Information service